Molecular characterization of turtle-like protein in whiteleg shrimp (Litopenaeus vannamei) and its role in Enterocytozoon hepatopenaei infection - Adrián E. Velázquez-Lizárraga; Pongsakorn Sukonthamarn; Wisarut Junprung; Zittipong Nanakorn; Ornchuma Itsathitphaisarn; Pattana Jaroenlak; Anchalee Tassanakajon (Fish & Shellfish Immunology, 2023)

Decay of the glycolytic pathway and adaptation to intranuclear parasitism within Enterocytozoonidae microsporidia - Dominic Wiredu Boakye; Pattana Jaroenlak; Anuphap Prachumwat; Tom A. Williams; Kelly S. Bateman; Ornchuma Itsathitphaisarn; Kallaya Sritunyalucksana; Konrad H. Paszkiewicz; Karen A. Moore; Grant D. Stentiford; Bryony A. P. Williams (Environmental Microbiology, 2017)
Summary Glycolysis and oxidative phosphorylation are the fundamental pathways of ATP generation in eukaryotes. Yet in microsporidia, endoparasitic fungi living at the limits of cellular streamlining, oxidative phosphorylation has been lost: energy is obtained directly from the host or, during the dispersive spore stage, via glycolysis. It was therefore surprising when the first sequenced genome from the Enterocytozoonidae – a major family of human and animal‐infecting microsporidians – appeared to have lost genes for glycolysis. Here, we sequence and analyse genomes from additional members of this family, shedding new light on their unusual biology. Our survey includes the genome of Enterocytozoon hepatopenaei , a major aquacultural parasite currently causing substantial economic losses in shrimp farming, and Enterospora canceri , a pathogen that lives exclusively inside epithelial cell nuclei of its crab host. Our analysis of gene content across the clade suggests that Ent. canceri 's adaptation to intranuclear life is underpinned by the expansion of transporter families. We demonstrate that this entire lineage of pathogens has lost glycolysis and, uniquely amongst eukaryotes, lacks any obvious intrinsic means of generating energy. Our study provides an important resource for the investigation of host‐pathogen interactions and reductive evolution in one of the most medically and economically important microsporidian lineages.